The Influence of Awareness and Communication on Occupational Safety and Health at Pangeran Beach Hotel Padang - Revayani, Amara; Hermansyah (Journal of Multidimensional Management, 2025)
This study investigates the influence of awareness and communication on occupational safety and health (OSH) among employees at Pangeran Beach Hotel Padang. Using a quantitative approach, data were collected through questionnaires distributed to 108 employees and analyzed using multiple linear regression with SPSS version 26.0. The results reveal that both awareness and communication have a positive and significant effect on OSH, both individually and simultaneously. Awareness positively contributes to employees’ adherence to safety procedures, while effective communication enhances the dissemination and understanding of safety information across organizational levels. Together, these variables explain 29.2% of the variance in OSH, indicating that other factors such as work environment, safety culture, and personal protective equipment usage may also play substantial roles. These findings highlight the importance of integrating awareness-building initiatives with effective communication strategies to foster a sustainable safety culture in the hospitality industry